(3EOGQI GdCYeGd GdOhdjIs - (3CHh bMa(B, (3YHO GdSdGes ((3GdEScfOQjIs (3GdOGQ GdLGeYjIs, 2005)
(3bVjI GdYhdeI, GdYhdeI GdJfhjQ GdRGFa, LOhi GdGSJKeGQGJ GdCLfHjI, JMdjd hGSJWdGY GdGJLGgGJ fMh GdYhdeI Ch GdJOhjd hGdNjGQGJ GdHOjdI, eaghe GdGOGQI GdOhdjI h JUfja GdTQcGJ Ydi GdeSJhi GdOhdj, HjFI GdGOGQI GdOhdjI, GdfeGPL h GdUjZ GdLOjOI ddefXeGJ Ydi GdeSJhi Gdchfj(B/ (3cja fOjQ YHQ KbGaGJ eNJdaI(B- (3GdGOGQI aj KbGaGJ eJHGjfI, EOGQI MVGQI(B- (3KbGaI GdTQcI, EOGQI GdeNGWQ GdSjGSjI hGdeaGhVGJ, GdJNWjW GdGSJQGJjLj, WQb heSGQGJ ZRh GdCShGb GdOhdjI, JfXje hJhLjg GdGSJKeGQGJ GdGLfHjI (B- (3GdSjGSGJ hGdGLQGAGJ h GdMhGaR HGdOhd GdeVjaI, JfXje GdYedjGJ GdOhdjI, EJNGP GdbQGQGJ h GdQbGHI, bjGS GdQaY GdGSJQGJjLj hEWGQ GdGSJQGJjLjI GdCMdGa GdchfjI, GdSdhc GdJfXjej h GOGQI GdehGQO GdHTQjI(B- (3GdOGaYjI hGdbjGOI, GdNUGFU GdGSJQGJjLjI ddGSJKeGQ GdCLfHj GdeHGTQ hYdGbJgG HHdO GdefTC heSJhi GdCOGA aj eUQ, CSYGQ Jehjd Hjf aQhY GdTQcGJ GdYGdejI, GdJMGdaGJ GdGSJQGJjLjI Hjf GdTQcGJ GdBSjh(B-(3YQHjI, GdGSJMhGP hGdGfOeGL GdOhdj aj Xd eQGYj GdYhdeI(B- (3GdhGbY GdMGdj hGdLOhi hGdeONd hGdebJQM ddJaVjd(B.s
Keywords: (3EOGQI GdCYeGds